Wedding cake murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery,, 2016)
Everyone in Lake Eden, Minnesota, may have had their doubts, but at long last, Hannah Swensen is getting married! Hannah is thrilled to be marrying Ross Barton, her college crush. And her excitement only grows when she learns he'll be able to join her on her trip to New York City for the Food Channel's dessert chef contest. They get a taste of the Big Apple before Hannah wins the Hometown Challenge and the producers bring all the contestants to Lake Eden to tape the remainder of the show. It's nerve-wracking enough being judged by Alain Duquesne, a celebrity chef with a nasty reputation. But it's even more chilling to find him stabbed to death in the Lake Eden Inn's walk-in cooler-before he's even had a chance to taste Hannah's Butterscotch Sugar Cookies! Now Hannah has not only lost her advantage, she'll have to solve a mystery with more layers than a five-tiered wedding cake.